การบริหารตามหลักพรหมวิหารธรรมขององค์การบริหารส่วนตำบลชัยพฤกษ์ ตำบลชัยพฤกษ์ อำเภอเมืองเลย จังหวัดเลย - มาเมือง, ไพฑูรย์ (วารสารศรีล้านช้างปริทรรศน์; Vol 7 No 1 (2021): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 7 ฉบับที่ 1 (มกราคม - มิถุนายน 2564), 2021)
การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อ (1) ศึกษาการบริหารตามหลักพรหมวิหารธรรมขององค์การบริหารส่วนตำบลชัยพฤกษ์ ตำบลชัยพฤกษ์ อำเภอเมืองเลย จังหวัดเลย (2) เปรียบเทียบการบริหารตามหลักพรหมวิหารธรรมขององค์การบริหารส่วนตำบลชัยพฤกษ์ ตำบลชัยพฤกษ์ อำเภอเมืองเลย จังหวัดเลย  จำแนกตามอายุ และระดับการศึกษาที่แตกต่างกัน กลุ่มตัวอย่างที่ใช้ในการศึกษาวิจัยครั้งนี้  คือ ประชาชน ในเขตพื้นที่องค์การบริหารส่วนตำบลชัยพฤกษ์  ตำบลชัยพฤกษ์ อำเภอเมืองเลย จังหวัดเลย จำนวน 361 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล คือ แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่  ค่าความถี่ (Frequency) ค่าร้อยละ (Percentage) ค่าเฉลี่ย (Mean) และค่าเบี่ยงเบนมาตรฐาน (Standard Deviation) และวิเคราะห์เปรียบเทียบการบริหารตามหลักพรหมวิหารธรรมขององค์การบริหารส่วนตำบลชัยพฤกษ์ ตำบลชัยพฤกษ์ อำเภอเมืองเลย จังหวัดเลย โดยใช้สถิติ One – Way ANOVA                ผลการวิจัยพบว่า   1) การบริหารตามหลักพรหมวิหารธรรมขององค์การบริหารส่วนตำบลชัยพฤกษ์ ตำบลชัยพฤกษ์ อำเภอเมืองเลย จังหวัดเลย โดยภาพรวม อยู่ในระดับมาก เมื่อพิจารณาเป็นรายด้านพบว่า พบว่า ความคิดเห็นด้านอุเบกขา อยู่ในระดับมากที่สุด รองลงมาคือ ด้านกรุณาอยู่ในระดับมากที่สุด และด้านที่มีความคิดเห็นต่ำสุด คือ ด้านเมตตา             2) ผลการเปรียบเทียบการบริหารตามหลักพรหมวิหารธรรมขององค์การบริหารส่วนตำบลชัยพฤกษ์ ตำบลชัยพฤกษ์ อำเภอเมืองเลย จังหวัดเลย จำแนกตามอายุ และระดับการศึกษา พบว่า อายุ และระดับการศึกษาของประชาชนแตกต่างกัน มีความคิดเห็นไม่แตกต่างกัน                  The objectives of the research article were (1) to study the administration based on Brahmavihāra-dhamma (Four Holy Abidings or Four Sublime States of Mind) of Chiyaphrek Sub-district Administrative Organization, Mueang district, Loei province, and (2) to compare the opinions of people on the Brahmavihāra-dhamma-based administration of Chiyaphrek Sub-district Administrative Organization, Mueang district, Loei province, classified by their age and educational level. The population of the research was a total of people dwelling in eight communities in Chiyaphrek sub-district, Mueang district, Loei province; 361 samples were selected through the sampling method. The instrument used for data collection was the rating scale questionnaire; the statistics used for data analysis comprised of frequency, percentage, mean, and standard deviation whereas the statistics used for the hypothetical test were the t-test and one-way analysis of variance (ANOVA).                The findings of the research were as follows:                1) The Brahmavihāra-dhamma-based administration of Chiyaphrek Sub-district Administrative Organization, Mueang district, Loei province, was found to be overall at a high level. Separately considered in the descending order, equanimity or neutrality (Upekkhā) was found to be at the highest level of mean scores, followed by compassion (Karunā), altruistic joy (Muditā) and loving-kindness (Mettā) were found to be at the lowest level.                2) The comparison of people’s opinions on the Brahmavihāra-dhamma-based administration of Chiyaphrek Sub-district Administrative Organization, Mueang district, Loei province, classified by their age and educational level, was found that the opinions of people with different age and educational level were found not to be different.